Performance and operation of the calorimetric trigger processor of the NA62 experiment at CERN SPS. (21st April 2017) - Ammendola, R.; Barbanera, M.; Battista, D.; Bizzarri, M.; Bonaiuto, V.; Ceccucci, A.; Checcucci, B.; Simone, N. De; Fantechi, R.; Federici, L.; Fucci, A.; Lupi, M.; et al.
Abstract: The NA62 experiment at the CERN SPS aims at measuring the branching ratio of the very rare kaon decay K +  → π +  ν ν̄ (expected 10 −10 ) with a 10% background. Since an high-intensity kaon beam is required to collect enough statistics, the Level-0 trigger plays a fundamental role in both the background rejection and in the particle identification. The calorimetric trigger collects data from various calorimeters and it is able to identify clusters of energy deposit and determine their position, fine-time and energy. This paper describes the trigger system setup during the 2016 physics data taking. A newly implemented cluster counting algorithm is also presented.